ANALISIS PERENCANAAN PAJAK (TAX PLANNING) PADA PEMBAYARAN PAJAK PENGHASILAN PADA PT. PANCA GLOBAL SECURITIES TBK - Purba, Rosanna (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
As a source of tax state revenue is used to finance government expenditure,construct and improve infrastructure, provide education and health facilities, and financing activities in the government provides for the needs that can not be provided by the private sector in the form of goods public goods. As for place in this study were PT. Panca Global Securities Tbk, tax plannng policies on corporate income tax. The purpose of this research is to analyze the application of tax planning in tax payments and to analyze the application of tax planning to PT. Panca Global Securities Tbk. The method used in this method is a descriptive approach which s one of the types of re search that use numberic data and emphasizes the research process on measuring objectve results using statistical analysis. The results were obtained as to minimize the burden of the tax benefits as a component of cost so as to save the cash flows out and can estimate the cash requirements to pay the outstanding tax burden as well as to determine the exact time of payment so that the company can budget accurately cash. Orderly implementation of administrative systems and neat to run smoothly as planned resulting in tax savings to support the company’s strategy to improve performance. The better the factors supporting tax planning, then the optimal tax burden can be saved as well as the smaller the risk of sanction or penalty taxes that will be suffered by the company. Keywords: tax planning, and payment of corporate income tax